The effects of climate change on masculinity: a case of Zindowe village, Mberengwa district - Chisoro, Elizabeth (Midlands State University, 2014)
Climate change is among the most contemporary issues affecting many people in several parts of the word. In view of climate change and gender it can be noted that it has contributed immensely to change in carrying out of masculine livelihood strategies by men in rural communities. This is so because most men are usually bread winners of families, and the effects are more pronounced in rural areas since there is dependency on natural resources or environment in addition to climate change sensitive practices like agriculture and livestock rearing. Ultimately this results in plummeting agricultural production which in the end paves way for poverty. Societies play a crucial role in determining or setting of parameters on how masculine or feminine gender roles should be. Therefore traditionally men in Zindowe village have been regarded as bread winners who are entitled to provide for their families, even in such difficult circumstances. In this scenario men opt for other alternative sources of livelihood. More often than not the activities that most men opt for are usually dangerous and criminal activities viewed to be risky yet at the same time have higher returns since they generate faster and more reliable earnings than agricultural production. Such activities include illegal mining, cross boarder jumping, theft and unlicensed omnibus operation. Some even succumb to alcoholism or suicide when they give up to the pressure associated with the role of a bread winner. This study managed to articulate challenges or problems caused by the above alternatives taken by men for they do not impinge on them only but women and children are also affected. Also of significance to this study is the revealing of gender mainstreaming in mitigation and adaptation measures of climate change so as to lessen the burden felt by both men and women through their gender roles, in this way gender equality is attained as both men and women would be included in the climate change and gender discourse. However, the challenge was the community relies more on external assistance like food aid from NGOs which is not sustainable. Another restrain in adaptation and mitigation is largely centered on lack of capacity and resources as money, however there are also other means used to adapt to climate change that are proving be helpful to like growing of drought resistant small grains as sorghum, crop diversification, climate change adaptation projects to mention but a few.